Penicillin induces alterations in glutamine metabolism in Streptococcus pneumoniae. Issue 1 (December 2017) - El Khoury, Jessica; Boucher, Nancy; Bergeron, Michel; Leprohon, Philippe; Ouellette, Marc
Abstract Penicillin is a bactericidal antibiotic that inhibits the synthesis of the peptidoglycan by targeting penicillin-binding proteins. This study aimed to assess through transcriptional profiling the stress response ofS .pneumoniae strains after exposure to lethal penicillin concentrations to understand further the mode of action of penicillin. Two experimental designs (time-course and dose-response) were used for monitoring the effect of penicillin on the transcriptional profile. The expression of some genes previously shown to be modulated by penicillin was altered, includingciaRH, pstS andclpL . Genes of theglnRA andglnPQ operons were among the most downregulated genes in the three strains. These genes are involved in glutamine synthesis and uptake and LC-MS work confirmed that penicillin treatment increases the intracellular glutamine concentrations. Glutamine conferred a protective role against penicillin when added to the culture medium. Glutamine synthetase encoded byglnA catalyses the transformation of glutamate and ammonium into glutamine and its chemical inhibition by the inhibitor L-methionine sulfoximine is shown to sensitizeS .pneumoniae to penicillin, including penicillin-resistant clinical isolates. In summary, a combination of RNA-seq and metabolomics revealed that penicillin interferes with glutamine metabolism suggesting strategies that could eventually be exploited for combination therapy or for reversal of resistance.